VOICES FROM THE TIDE: HUMAN RIGHTS, IDENTITY AND BELONGING IN AMITAV. GHOSH’S THE HUNGRY TIDE - Chaturvedi, Devesh Kumar; Sharma, Sheeba Himani (International Journal of Research -GRANTHAALAYAH, 2024)
The Hungry Tide by Amitav Ghosh examines several topics, such as identity, belonging, and human rights, against India's distinctive and frequently harsh Sundarbans. The book explores the lives of its characters, many of whom battle with societal injustice, displacement, and the quest for both individual and group identity. Ghosh brilliantly addresses a very complicated and historically charged issue in The Hungry Tide, shedding light on all of its dimensions. There are many concepts in The Hungry Tide, but none have a simple solution. The framework of science or business, where everything can be seen as black or white, is what Kanai and Piya prefer. Nothing is certain and everything in life is grey in the Sundarbans, where the tides alter the landscape every day. Since tigers are a protected species, killing a tiger that has been preying on a hamlet draws in government officials to administer punishment, even though tigers murder hundreds of people there each year. Any individual's essence is reduced to its most basic form in a setting where life is precarious. Amitav Ghosh allows his characters and society to transcend social boundaries.